Chemical characterization of the Bicchari ash pond and its impact around the Renusagar Thermal Power Plant, Sonbhadra district, Uttar Pradesh, India. Issue 3 (26th August 2021) - Pandey, Hemant Kumar; Kumar, Suraj; Mondal, Nepal Chandra; Rawal, Nekram
Abstract: The Renusagar thermal power plant is one of the most important power plants supplying electricity to the entire Hindalco Industry in Northern India. This plant causes soil and groundwater contamination due to the disposal of its fly ash in the Bicchari ash pond. An attempt has been made to characterize the ash pond and to study soil and groundwater contamination adjacent to the fly ash pond. In total, 11 groundwater samples and four samples each for the ash pond and soil were collected and analyzed to evaluate the impact of the pond on nearby soil and groundwater. Results show that the pond ash is a heterogeneous mixture of magnetic and nonmagnetic (such as mullite and quartz) compounds. Scanning electron microscopy of the pond ash reveals that most of the minerals present are spheroidal in shape, and a smaller size indicates the presence of silica. X‐ray fluorescence analysis of the soils reveals that in most of the samples zircoline has a relatively higher concentration, whereas silica is the major part of SiO2. Most groundwater samples are acidic, with an average pH of 6.73, which decreases the leaching of heavy metals. The concentration of Ca, Mn, and Fe is relatively high.